Internalisasi Nilai-nilai Retret untuk Motivasi Belajar Siswa Kelas XI SMA Katolik Frateran Malang - Topo, Lambertus; Setiyowati, Arbin Janu; Eva, Nur; Hutasuhut, Ida Yuliana (citeus, 2025)
Today's students' learning motivation tends to decline due to lack of attention to life values as the basis of human development in the educational process. This research aims to reveal three important things, namely; student learning motivation, students' hopes for retreat activities to increase their learning motivation, and the process of internalizing retreat values, namely honesty and humility towards student learning motivation. The design of this research is qualitative phenomenology. The main subjects of the research were class XI students at SMAK Frateran Malang who were drawn using purposive sampling. Data analysis techniques were carried out using domain analysis techniques, taxonomic analysis techniques, and theme analysis techniques. The research results show that students' learning motivation is greatly influenced by the economic and educational background of parents, the way and style of parental support at home, as well as the learning approach patterns used by teachers in the classroom. Students' hopes for retreats to increase learning motivation apparently return to the students themselves because the retreat mentoring pattern really uses retreat companions as facilitators. The approach in a retreat is different from the approach in the learning process in class. The retreat companion is a facilitator figure, the teacher in the class is an authority figure who oversees joint learning achievements.